Situation Report: Czechoslovakia, 30 September 1988 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Dumas Visits Czechoslovakia / by Peter Martin A Conference in Nijmegen on the Prague Spring and Dissent in Eastern Europe / by Jan Obrman The Revival of a Civil Society / by Jiri Pehe The Regime Rehabilitates National Day The Nationalist Card of the CPCS / by Jiri Pehe Aftermath of August 21 Demonstration in Prague / by Peter Martin Dissent Group Issues a Nine-Point Petition of "Czechoslovak Citizens" / by Peter Martin A "Public Debate" in Prague Broken Up by Police / by Peter Martin Vaclav Havel's Address to a Public Folk Festival / by Jiri Pehe Signs of Glasnost' within the Union of Czech Writers Reforming the Social Sciences